2006
DOI: 10.1097/01.shk.0000224722.65929.58
|View full text |Cite
|
Sign up to set email alerts
|

PROTECTION AGAINST PSEUDOMONAS AERUGINOSA PNEUMONIA AND SEPSIS-INDUCED LUNG INJURY BY OVEREXPRESSION of β-DEFENSIN-2 IN RATS

Abstract: Beta-defensin-2 (BD-2), a small cationic antimicrobial peptide, was first described to be an inducible defensin at the epithelial surfaces. In vitro studies have demonstrated that it may play a pivotal role in the anti-inflammatory immune response in addition to its antimicrobial activity. The purpose of this study was to evaluate the effect of overexpression of BD-2 on lung injury to crudely investigate whether the function of BD-2 in the lung attributed to both antimicrobial action and modulation of the immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 34 publications
1
33
0
1
Order By: Relevance
“…5 Meanwhile, in vivo study showed a protective role of overexpressed bdefensin 2 against sepsis via anti-inflammation activity. 31 Studies have shown that DEFB4 and DEFB103 as well as DEFB104 were polymorphic in copy number variation, [20][21][22] and the genomic copy number of DEFB4 correlated with the level of its transcript. 20 Copy number polymorphism of defensin may have a crucial role in inflammatory disease, which has been demonstrated in Crohn's disease.…”
Section: Snpsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Meanwhile, in vivo study showed a protective role of overexpressed bdefensin 2 against sepsis via anti-inflammation activity. 31 Studies have shown that DEFB4 and DEFB103 as well as DEFB104 were polymorphic in copy number variation, [20][21][22] and the genomic copy number of DEFB4 correlated with the level of its transcript. 20 Copy number polymorphism of defensin may have a crucial role in inflammatory disease, which has been demonstrated in Crohn's disease.…”
Section: Snpsmentioning
confidence: 99%
“…Consistent with this view were the findings indicating that defensins did suppress the release of proinflammatory cytokines and adhesion molecules in vivo. 29,31 Thus, DEFB1 could both play a direct antimicrobial role and have a modulating effect on the inflammatory response. In summary, DEFB1 plays an important role in the host immune response to severe sepsis.…”
Section: Snpsmentioning
confidence: 99%
“…IL-22 has recently been implicated in the preservation of epithelial integrity through its action on intercellular junctions and the synthesis of antimicrobial peptides (26,30). Among antimicrobial peptides, ␤-defensin-2 and cathelicidin have been reported to play a pivotal role in the control of P. aeruginosa infection (40)(41)(42). Since both antimicrobial peptides were strongly potentiated by C. albicans exposure, this mechanism could therefore participate in the protection.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8] The majority of prior studies focused on the pathophysiological effect of HBD-2 in respiratory infection, demonstrating activation of HBD-2 biosynthesis and release into the airway and plasma via bacterial or foreign microorganisms, and inflammatory cytokines stimulation following pneumonia or other lower-respiratory-tract infection. [9][10][11][12][13][14][15][16] However, few studies have examined the clinical implication of the elevated HBD-2 in community-acquired pneumonia (CAP), and whether HBD-2 predicts clinical outcomes in CAP. Therefore, this study evaluated the association between plasma HBD-2 concentration on admission and 30-day clinical outcomes in patients with CAP.…”
Section: Introductionmentioning
confidence: 99%